2017
DOI: 10.2147/ndt.s128432
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality as a predictor of self-efficacy and social support in patients with type 2 diabetes mellitus

Abstract: ObjectiveThe aim of this study was to estimate the prevalence of Type D personality and assess the relationship between this personality type and self-efficacy/social support in Chinese patients with type 2 diabetes mellitus (T2DM).Patients and methodsFrom January 1, 2014, to July 31, 2014, 532 consecutive patients with T2DM were recruited from two hospitals in Guangzhou, China. The participants completed questionnaires containing questions about sociodemographic characteristics, Type D personality, self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 33 publications
7
60
0
Order By: Relevance
“…The prevalence found is close to that found in other Asian countries such as the 18.2% prevalence of type D personality in type 2 diabetic patients in Chinese patients (Shao et al, 2017). Likewise, the prevalence of type D personality in Korean healthy, CHD, and hypertension groups was 27% (Lim et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prevalence found is close to that found in other Asian countries such as the 18.2% prevalence of type D personality in type 2 diabetic patients in Chinese patients (Shao et al, 2017). Likewise, the prevalence of type D personality in Korean healthy, CHD, and hypertension groups was 27% (Lim et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Focusing on two domains of type D personality, which are negative affectivity and social inhibition, an inverse relationship with medication self-efficacy was found. This finding can be supported by the result which both negative affectivity and social inhibition showed a negative association with selfefficacy (Shao et al, 2017). Also, there was a study reported that after discharge from the hospital for six months, 30% of patients who were type D personality have a significant lower medication adherence (Molloy et al, 2012).…”
Section: Discussionmentioning
confidence: 81%
“…Type D personality was associated with lower levels of social support in Danish and Dutch Type D participants with cardiac arrhythmias (Pedersen et al, 2009), Iranian myocardial infarction patients (Bagherian Sararoudi et al, 2011), and Indonesian patients with coronary heart disease (Ginting et al, 2016). Initial evidence in people with type 2 diabetes also suggested that individuals with Type D personality may also experience less social support (Nefs et al, 2012;Shao et al, 2017). Our study confirms these findings, and extends them to people with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In people with diabetes, Type D has been associated with suboptimal health behaviors (Conti, Carrozzino, Patierno, Vitacolonna, & Fulcheri, 2016;Nefs et al, 2015) and with higher HbA1c (X. Li, et al, 2017;Shao, Yin, & Wan, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation